15-LOX metabolites and angiogenesis: angiostatic effect of 15(S)-HPETE involves induction of apoptosis in adipose endothelial cells - Sasikumar J. Soumya; Sheela Binu; Antony Helen; Pallu Reddanna; Perumana R. Sudhakaran (PeerJ, 2014)
Inflammation is critical in the dysregulated growth of adipose tissue and associated vascular dysfunctions. 15-Lipoxygenase metabolites, important mediators of inflammation in adipose tissue during obese conditions, may contribute to codependence of inflammation and angiogenesis in adipose tissue. We have already reported the pro-angiogenic effect of 15(S)-HETE in adipose tissue. The present study was designed to understand the effect of 15(S)-HPETE, precursor of 15(S)-HETE, on angiogenesis in adipose tissue. Results showed that 15(S)-HPETE exerts an anti-angiogenic effect in adipose tissue. This was evidenced from decreased endothelial sprouting in adipose tissue explants, inhibition of angiogenic phenotype in adipose endothelial cells, decreased production of CD31 and VEGF in endothelial cells treated with 15(S)-HPETE. Further studies to examine the molecular mechanism of anti-angiogenic effect of 15(S)-HPETE showed that it inhibited cell survival signaling molecule Akt and anti-apoptotic Bcl-2 and also activated caspase-3 in adipose endothelial cells. These observations indicate that 15(S)-HPETE exerts its angiostatic effect in adipose tissue by inducing apoptosis of endothelial cells.